Desain Bilik Disinfektan Guna Mencegah Penularan Covid-19 Di Industri Galangan Kapal - Samuel Febriary Khristyson; Sulaiman Sulaiman; Suharto Suharto; Solichin Djazuli Sa’id; Eko Julianto Sasono; Budi Utomo; Bambang Sri Waluyo; Jerry Akbar Wijanarko; Aristo Bagus Jatmiko; Adi Kurniawan Yusim (Jurnal Pengabdian Vokasi, 2021)
Disinfectant Design To Prevent Covid-19 Transmission In Ship Building Industry: The world condition has a varied spike in Covid-19 cases. The new normal scenario has been prepared by the Indonesian government to take effect from 1 June 2020, where industries and services can operate according to health protocols. In general, in entering into this new normality, we must find a midpoint of importance between health and economics. The purpose of this paper is to explore the design of a disinfectant chamber adapted to the possible environment that can be applied in a shipyard. The design method used is to compile an existing hypothesis from previous research and field conditions data then poured into a design that represents the ideal disinfectant room design optimization to use. As a result, with the design method and concept, the ideal design for the area of operation is obtained. With materials that are easier to find in the market and simplified manufacturing costs, this product is superior to be applied in this shipyard. In comparison, the expected function value from the planning of this disinfectant room will be better or almost closer to the products on the market. However, in the application process, it is necessary to look at the capability and operational area of the place where this disinfectant booth will be located.